2005
DOI: 10.1111/j.1744-313x.2005.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the mutated Δ32 allele of the CCR5 gene in a Sicilian population

Abstract: The CCR5 gene encodes a cell-surface chemokine receptor molecule that serves as a co-receptor for macrophage-tropic strains of human immunodeficiency virus type 1 (HIV-1). A mutation in this gene may alter the expression or the function of the protein product, thereby altering chemokine binding and/or signalling or HIV-1 infection of cells that normally express CCR5 protein. Individuals homozygous for a 32-bp deletion allele of CCR5 (CCR5 delta32), heritable as a Mendelian trait, are relatively resistant to HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
(14 reference statements)
2
6
0
Order By: Relevance
“…In India CCR5Δ32 allele was absent in most of the populations of India, except some populations of Northern/western India where it could have been introduced by Caucasian gene flow (Majumder and Dey, 2001). CCR5Δ32 deletion might alter the expression or function of the protein (Sidoti et al, 2005). In the present study, only four (5.0%) of the breast cancer patients were reported to be heterozygous for CCR5Δ32 mutation similar to 3.47% CCR5Δ32 heterozygous breast cancer patients reported in Brazilian population (Aoki et al, 2009).…”
Section: Discussionsupporting
confidence: 65%
“…In India CCR5Δ32 allele was absent in most of the populations of India, except some populations of Northern/western India where it could have been introduced by Caucasian gene flow (Majumder and Dey, 2001). CCR5Δ32 deletion might alter the expression or function of the protein (Sidoti et al, 2005). In the present study, only four (5.0%) of the breast cancer patients were reported to be heterozygous for CCR5Δ32 mutation similar to 3.47% CCR5Δ32 heterozygous breast cancer patients reported in Brazilian population (Aoki et al, 2009).…”
Section: Discussionsupporting
confidence: 65%
“…From our study, it was found that the CCR5Δ32 allele frequency in Sicilian RR-MS patients ( fr = 0.06) is comparable to that found in the general population ( fr = 0.06) [40]. Our results, on the one hand, are consistent with those of some studies [20] and, on the other hand, are not confirmed by other studies [29, 31].…”
Section: Discussionsupporting
confidence: 73%
“…CCR5 plays an important role in the recruitment of macrophages, monocytes and T cells at inflammation sites (23), driving an immune response involving a Th1 cytokine pattern (24). CCR5D32 deletion may alter the expression or function of the protein product (25).…”
Section: Discussionmentioning
confidence: 99%